O direito de reivindicar e o dever de (des) obedecer: mulheres transexuais políticas do Mercosul - Moura, Ismarina Mendonça de (2022)
In this research, we present MERCOSUR political transsexual women from the audiovisual corpus in YouTube videos during the period (2016-2020. The objective of this research is to problematize, discuss and analyze the materialization of discourses in MERCOSUR political transsexual women, establishing questions theoretical-analytical analysis that can reveal discursive enunciabilities and their decipherments in audiovisualities. For this, we analyzed twelve audiovisual files that are divided and separated into two types of formations: a) legislative assemblies (or public hearings): are trans women in the political institutional field, speaking in the legislative space; and b) in internet or television interviews: where they present these subjects in interactive spaces, in interviews, discussing issues around themselves and the LGBTQIA+ community. The methodological procedures adopted for the chaining of the audiovisual series refer to Foucauldian notions of the work The Archeology of Knowledge by Michel Foucault, basically from the chapter The formation of objects, together with the concept of “audiovisualities” according to Milanez (2019) in his book/ work Audiovisualities: elaborating with Foucault. Among the results: we obtained the historical elements that made possible the irruption of the political transsexual subject causing developments: the right to vote for women, the military dictatorships in the MERCOSUR countries, the creation of the contraceptive pill as a female contraceptive method, the fight around AIDS, the LGBTQIA+ movements; We found that MERCOSUR political transsexual women enter politics with an acquired self-care and this self-care promotes a care for the other, a care for subjects that are erased, made invisible by society. Thus, the subjects envision a change in this system formed to harm, erase and make invisible the subjects on the sidelines. So they, political transsexual subjects seek to change the rules and laws that manage society in order to end this system; in relation to parrhesia, we reveal that: a) parrhesia appears characterized through discourses produced on different subjects, highlighting actions and utterances as a way of life of transsexual subjects; b) when women politicians practice telling the truth, they already do so knowing the possibilities and undetermined risks they may suffer as a counter-action of their interlocutors; c) indirectly MERCOSUR subjects operate within the parrhesiastic characteristics: virtue, duty and technique. We conclude that MERCOSUR political transsexual women are in the political field because the right to claim and the duty to (dis)obey were decisive for the composition of the subjectivities of these subjects as politicians.